LEGAL POLITICS OF FORMULATION OF THE CRIMINAL ACT OF DOMESTIC VIOLENCE AS A SPECIAL FORM OF CRIMINAL ACT - Dewanti Oktaferina Putri Damadika (CV. RADJA PUBLIKA, 2025)
Domestic violence, such as physical, psychological, sexual, and economic violence, is a form of crime that occurs in a household where the perpetrator and victim come from the same household. The government's penal policy in resolving domestic violence is formed in the codification of positive legal norms (positif wettelijk), by implementing Law Number 23 of 2004 concerning the Elimination of Domestic Violence. This regulation demonstrates the government's attention to human rights (HAM), gender, non-discrimination, and protection. victims of domestic violence.